Reply to Cotrim, N.; Cotrim, C. Is It Wise to Forget Exercise Stress Echocardiography in the Study of Chest Pain in Children? Comment on “Huang, S.-W.; Liu, Y.-K. Pediatric Chest Pain: A Review of Diagnostic Tools in the Pediatric Emergency Department. Diagnostics 2024, 14, 526” - Szu-Wei Huang; Ying-Kuo Liu (Diagnostics)
We sincerely thank Nuno Cotrim and Carlos Cotrim for their valuable comments on our article [...]